Approaches to the method of granulation of fly ash of power plants - Natalya I. Goryacheva; Alexey V. Poltavets; Alexander R. Bogomolov; Elena Yu. Temnikova (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The research is aimed at reducing the impact of deficiencies (dusting) when involving in circulation fly ash, which prevents the wider use of valuable secondary raw materials in the production of demanded products. The direction of work corresponds to the Comprehensive Waste Disposal Plan for coal-fired power plants and boiler houses, approved by the Decree of the Government of the Russian Federation dated 06/15/2022 No. 1557-R. Aim. Development of an optimal technology for the production of granules from fly ash of Kemerovo GRES using two types of substances of a similar nature as a binder, depending on the concentration of the binder in an aqueous solution and the delay time of strength gain and abrasion index. Object. A granulate or pellet made of fly ash based on a binder of experimental aluminosilicate glue and liquid sodium glass "Diola-53". Methods. Strength tests were carried out on a hydraulic press according to SS 8929-2020 and the abrasion index of a large filler in a shelf drum was determined out according to SS 9758-2012. Two methods of granulation of fly ash were used: 1) two-stage – preparation (cooking) of aluminosilicate glue from fly ash and granulation; 2) one-stage – granulation using market liquid glass. Liquid aluminosilicate glue was produced experimentally in a container using a flask heater and a mixing device. Results and conclusions. The authors have established the differences in the delay time of strength gain and the abrasion index of granules obtained by two methods based on fly ash from Kemerovo Urban District Power Plant using aluminosilicate glue and liquid sodium glass "Diola-53" as a binder. They found the dependences of the delay time of strength gain and the abrasion index of granules on the concentration (fraction) of an aqueous solution of the binder. The specific costs for the production of granules for each binder and its proportion in an aqueous solution are determined. Granulate from fly ash based on a binder: experimental aluminosilicate glue and liquid sodium glass "Diola-53", can be transported without dusting by any type of transport and serve as a potential raw material for cement production and a component in concrete production.